2005
DOI: 10.1007/s10517-005-0473-1
|View full text |Cite
|
Sign up to set email alerts
|

Electron Probe Microanalysis of Potassium and Sodium in Clonogenic Culture of Human Neural Stem Cells

Abstract: The mean potassium and sodium concentrations and distribution of potassium in clonogenic culture of human neural stem cells (neurosphere) were estimated by means of electron probe microanalysis. High sodium concentration was typical of undifferentiated cells. Potassium was irregularly distributed in the test structure. Our results confirm published data on heterogeneous morphological structure of neurospheres.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2006
2006
2006
2006

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Even with consideration for the impact of extracellular space, high concentration of sodium, not characteristic of a differentiated cells, attracts special interest. It was shown that potassium was unevenly distributed in a neurosphere [3]. This observation does not contradict the heterogeneous structure of the neurosphere demonstrated at an ultrastructural and morphological levels [19].…”
Section: Group Sodium Potassiummentioning
confidence: 68%
See 1 more Smart Citation
“…Even with consideration for the impact of extracellular space, high concentration of sodium, not characteristic of a differentiated cells, attracts special interest. It was shown that potassium was unevenly distributed in a neurosphere [3]. This observation does not contradict the heterogeneous structure of the neurosphere demonstrated at an ultrastructural and morphological levels [19].…”
Section: Group Sodium Potassiummentioning
confidence: 68%
“…An example of this effective application is analysis of human clonogenic neurospheres obtained by neural stem cell culturing [3].…”
Section: Group Sodium Potassiummentioning
confidence: 99%